Beach thriller - Day, Jamie (St. Martin's Press, 2026)
"The ultimate summer suspense novel, this book-within-a-book thriller is perfect for beach read lovers everywhere! It's been nearly twenty years since Holly last visited the charming town of Beauport, Massachusetts, and it remains as enchanting as she remembers. The boardwalk is still lively with tourists browsing shops and exploring art galleries. Crescent Beach looks unchanged, with light reflecting off the cold Atlantic waves. However, Holly's painful memories still linger. She feels intense pangs of guilt, just as strong now as they were then-when her sister tragically died right here in Beauport, and Holly did nothing to stop it. As a struggling writer, declining sales have forced Holly out of her cherished New York apartment. Now, she must live in the last place she wants: her family's long-abandoned beach house, where she last saw her sister alive. Holly arrives on a mission from her literary agent to write a best-selling book. But she's not the only one with an agenda. Someone is watching Holly's every move from the shadows. The Watcher sees all and knows what Holly doesn't. Some secrets must remain buried. With writer's block and a long-neglected cottage to fix, Holly feels as though she's drowning in financial burdens. Reinventing herself won't be easy, but she does make some helpful friends along the way. There's Gail, the property-obsessed realtor who introduces her to a friendly handyman named Ethan. The local psychic, Serena, also supports her, although she warns of impending danger. Then there's the young, mysterious Jade, a runaway teen in Beauport on a secret mission. Jade has nowhere to go, so Holly takes her in. When Jade lands a job with the powerful Carmichael family, Holly feels overwhelmed with dread. The Carmichaels' influence in town has waned over the years, but they will always have a dark connection to her tragic past. Their hidden secrets could also endanger young Jade. As threats from the ominous Watcher become increasingly sinister, Holly realizes that, even though the distant past is a faint echo, it is still close enough to be deadly"-- Provided by publisher.